Determination of Chromium in Chinese Herbal Medicine with Matrix Modifier by Graphite Furnace Atomic Absorption Spectrometry - Feng, Shaoping; Fan, Aiping; Xu, Chun; Liu, Wei; Huang, Zhaolong; Xu, Shijuan; Wu, Na (Asian Journal of Chemistry, 2015)
A rapid analytical method of graphite furnace atomic absorption spectrometry has been developed for determination of chromium present in Chinese herbal medicine. The effect of digestion method on sample preparation was discussed and the determination conditions by graphite furnace atomic absorption spectrometry were optimized, with 2 % (NH4)2HPO4 was used as matrix modifier, respectively. Under the optimum conditions, the linear range of chromium was 0 to 10 μg/L, the correlation coefficient was 0.9990 and the detection limit was 0.056 μg/L. The precision relative standard deviations were between 1.86 and 2.69 % for determining of chromium and the spike recoveries range from 97.47 to 101.90 %. These results indicated that the method is reasonable suitable for trace analysis.